Steady Boundary Layer Flow Of Nanofluid With Microorganism - Amirsom, Nur Ardiana (2020)
In this thesis, an analysis of two and three dimensional laminar convective boundary layer flow of a nanofluid with microorganism is investigated. It involves two and three dimensional laminar convective external boundary layer flow with heat and mass transfer under various physical configurations as well as geometries. The parameters that involved in this research are consist of magnetic field, heat generation/absorption, velocity slip, thermal slip, mass slip, microorganisms slip, viscosity, thermal conductive, mass diffusivity, and microorganism diffusivity. Melting heat transfer rate, Stefan blowing and multiple boundary conditions are taken into account. The fluid is characterized to be Newtonian, non- Newtonian, viscous, incompressible, magnetohydrodynamic and has constant or variable physical properties. Steady boundary layers are considered and appropriate transformations are used to transform the partial differential equations into nonlinear ordinary differential equations. The transformed equations are solved numerically using the bvp4c in Matlab for various values of the controlling parameters. Graphs are plotted to display the effect of the controlling parameters on the dimensionless velocity, viscosity, temperature, concentration (nanoparticle volume fraction), microorganism as well as skin friction factor, rate of heat, rate of mass transfer and rate of motile microorganism. The numerical solution for the skin friction factor, rate of heat, rate of mass transfer and rate of motile microorganism are generated for various values of the parameters. The flow field and other quantities of physical interest are found to be significantly influenced by the controlling parameters. A comparison with previously published work is carried out and the results are found to be in a good agreement.